Why do the Acehnese migrate? A study of the Hikayat Ranto from the socio-cultural perspective of Acehnese society - Mukhlis Mukhlis; Herman Rusli; Budi Arianto (Universitas Syiah Kuala, 2024)
This qualitative research focuses on linguistic texts as the subject of investigation, the Hikayat Ranto, written by Leube Isa and translated by Ramli Harun. The Acehnese people are renowned for their successful migration. In almost every region, within and outside Indonesia, one can find traces of Acehnese migrants. This article examines Acehnese societys social and cultural aspects as successful migrants who have explored various regions. Two fundamental questions addressed are (1) Why do Acehnese people choose to migrate? (2) What are the social characteristics of Acehnese people who migrate versus those who stay in their hometowns? These questions shed light on the culture of Acehnese society from a social and religious perspective. The data source for this study is the Hikayat Ranto. This earliest literary work narrates the tradition of migration in Acehnese society. Text analysis is conducted using coding methods with a hermeneutical approach. The study reveals that this hikayat (1) is one of the earliest literary texts that portray the social-religious aspects of Acehnese society concerning the facets of migration, which has become a tradition, (2) shows that migration tradition in Acehnese society occurs due to reasons related to family, education, and religion, and (3) demonstrates the social-religious characteristics of Acehnese society concerning the tradition of migration depict human-to-human and human-to-God relationships. These findings highlight how migration in Acehnese society is deeply rooted in both social bonds and unworldly devotion, reflecting their communal and cultural characteristics as both social beings and religious individuals.